2023
DOI: 10.1080/0886022x.2023.2222841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sacubitril-valsartan in patients undergoing maintenance dialysis

Abstract: : Objectives Data on angiotensin receptor-neprilysin inhibitor (ARNI) sacubitril-valsartan (SV) in patients undergoing maintenance dialysis is scarce. Our study aimed to investigate the effect of SV on patients undergoing dialysis. Methods We retrospectively reviewed the data of end-stage kidney disease (ESRD) patients undergoing either peritoneal dialysis (PD) or hemodialysis (HD) in our center. A total of 51 patients receiving SV treatment were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Studies have reported that echocardiographic parameters after SV initiation did not improve; however, the rate of improvement in LVEF was higher in the SV group than in the control group (26,27). This study has several limitations.…”
Section: Discussionmentioning
confidence: 78%
“…Studies have reported that echocardiographic parameters after SV initiation did not improve; however, the rate of improvement in LVEF was higher in the SV group than in the control group (26,27). This study has several limitations.…”
Section: Discussionmentioning
confidence: 78%
“…Three of the above studies reported side effects of hyperkalemia, with one study finding that sacubitril/valsartan did not increase serum potassium levels (4.6 ± 0.8 to 4.5 ± 0.7 mmol/L, p = 0.765) 13 . Ding et al, 10 reported a slightly higher, yet non‐significant, rate of hyperkalemia following sacubitril/valsartan therapy (19.6% vs. 27.5%, p = 0.350). Wang B et al 14 observed no hyperkalemia following sacubitril/valsartan therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 9 reported the efficacy and safety of sacubitril/valsartan in 23 patients with heart failure undergoing hemodialysis treatment, noting a reduction in serum troponin T levels and an improvement in left ventricular heart function after a follow‐up period of 4 months. A retrospective cohort study showed that sacubitril/valsartan can reduce the levels of B‐type natriuretic peptide and N‐terminal pro‐B‐type natriuretic peptide 10 . A prospective before‐and‐after study found that sacubitril/valsartan‐based therapy significantly reduced mean sitting systolic and diastolic blood pressure as well as improved cardiac remodeling parameters 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tổng cộng có 7 nghiên cứu với 447 bệnh nhân, thời gian công bố từ 2021 -2023, đã được đưa vào phân tích gộp (Bảng 1). 3,[6][7][8][9][10][11] Chú thích: :không được báo cáo; X ̄: trung bình; median: trung vị; SD: độ lệch chuẩn; IQR: khoảng tứ phân vị.…”
Section: Kết Quả Nghiên Cứuunclassified